Improving Employee Performance through Job Satisfaction, Engagement, and Organizational Support - Harindra Deny Prasetyo; Sutianingsih, Sutianingsih (Cita konsultindo, 2025)
This study aims to analyze the influence of job satisfaction, employee involvement, and organizational support on employee performance at PT BPR BKK Boyolali. The quantitative approach was used by a survey method through a questionnaire distributed to all 180 employees of PT BPR BKK Boyolali. The data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results of the structural model analysis show that job satisfaction has a positive and significant effect on employee performance. Similarly, employee engagement has a positive and significant effect on employee performance. Finally, organizational support also has a positive and significant effect on employee performance. This model is able to explain 72.6% variation in employee performance.